2012
DOI: 10.1111/j.1748-1716.2011.02380.x
|View full text |Cite
|
Sign up to set email alerts
|

Not only accumulation, but also saturation status of intramuscular lipids is significantly affected by PPARγ activation

Abstract: These findings support the conclusion that not only the change in total lipid content (DAG and TAG), but also FA composition is affected by rosiglitazone in an animal model of high-fat-diet-induced insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
3
31
1
Order By: Relevance
“…Furthermore, the primary function of PGZ is to increase the IMF deposition, and improvement of the meat flavor and taste has already been proven in pigs . Intensive research has ascribed the mechanism to the role of PGZ as an affinity ligand of PPAR γ , promoting adipocyte proliferation and fat accumulation . Undoubtedly, we found that supplementation with 7.5 mg kg −1 PGZ and 15 mg kg −1 PGZ increased the IMF by 14.14% and 20.37%, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, the primary function of PGZ is to increase the IMF deposition, and improvement of the meat flavor and taste has already been proven in pigs . Intensive research has ascribed the mechanism to the role of PGZ as an affinity ligand of PPAR γ , promoting adipocyte proliferation and fat accumulation . Undoubtedly, we found that supplementation with 7.5 mg kg −1 PGZ and 15 mg kg −1 PGZ increased the IMF by 14.14% and 20.37%, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, some of these studies suggested also that, not only DGs accumulation may affect insulin signalling but along with increased saturation status of FA present in this fraction is deleterious (Chabowski et al . ). However, there is still a matter of debate whether saturation status of FA species present in intracellular lipid fraction influences insulin signalling (Wakelam ).…”
Section: Discussionmentioning
confidence: 97%
“…Although baseline expression of muscle PLIN5 is strongly reduced in PPARα knockout mice, HFD-mediated up-regulation of PLIN5 is not prevented as well in these transgenic mice23. It is still unclear how HFD promotes the up-regulation of muscle PLIN5 but this may be under the control of PPARγ which contribute to lipid accumulation in skeletal muscle during high fat feeding36. Other transcription factors related to lipid storage may be involved.…”
Section: Discussionmentioning
confidence: 99%